Several Pythium species cause crown and root rot on cannabis (Cannabis sativa L., marijuana) plants grown under commercial greenhouse conditions. Issue 1 (2nd January 2022) - Punja, Zamir K.; Scott, Cameron; Lung, Samantha
Abstract: Cannabis ( Cannabis sativa L., marijuana) plants with symptoms of crown rot, root decay, wilting and plant death were sampled during 2018 and 2019 from seven licensed production greenhouses. Affected tissues from 140 diseased plants were surface-sterilized and plated onto potato dextrose agar. Ninety-five isolates morphologically resembling Pythium species were subcultured and subjected to PCR of the ITS1-5.8-ITS2 region of ribosomal DNA. The following species were identified based on >99% sequence identity to reference isolates in GenBank: P. myriotylum (43 isolates), P. dissotocum (35 isolates), P. aphanidermatum (3 isolates) and Globisporangium ultimum (syn. P. ultimum ) (2 isolates). A fifth species – P. catenulatum (12 isolates), was distinguished from P. rhizo-oryzae using the cytochrome oxidase c subunit I (COI) sequence. Cannabis licensed production facilities in British Columbia had all five species present, while P. dissotocum was found in two facilities in Ontario, and P. myriotylum was present in one facility in northern California. Isolates selected to represent each Pythium species were grown on potato dextrose agar at 25°C and they all showed comparable colony growth after 6 days. The same isolates caused root browning, decay and stunting of cannabis plants grown in a coco: perlite potting medium. Plant mortality was similar after 21 days but rates of disease progression varied depending on the isolate tested. Wounding of roots and prolonged periods of saturation enhanced disease development. These results demonstrate for the first time that crown and root rot on greenhouse-grown cannabis plants can be caused by up to five Pythium species.